2013
DOI: 10.3109/10715762.2013.804623
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal plasma treatment is associated with changes in transcriptome of human epithelial skin cells

Abstract: Non-thermal atmospheric pressure plasma has recently gained attention in the field of biomedical and clinical applications. In the area of plasma medicine research, one promising approach is to promote wound healing by stimulation of cells involved. To understand basic molecular and cellular mechanisms triggered by plasma treatment, we investigated biological effects of an argon plasma jet kinpen on human epithelial skin cells. For assessment of transcriptome changes cell culture medium was plasma treated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 82 publications
3
57
0
4
Order By: Relevance
“…The approach enabled a quick and reproducible treatment of cells in a 96 well plate and allowed an easy correlation with chemical assays. In vitro/ex vivo findings in different model systems of Bekeschus, 38 Schmidt, 39 and Wende et al 21 further indicated, that a separate treatment of liquids provokes the same biological effect as a direct treatment at least for the kinpen. The same effect has been observed for the plasma jet studied in this work (see Fig.…”
Section: A Motivation Of Treatment Approachmentioning
confidence: 99%
“…The approach enabled a quick and reproducible treatment of cells in a 96 well plate and allowed an easy correlation with chemical assays. In vitro/ex vivo findings in different model systems of Bekeschus, 38 Schmidt, 39 and Wende et al 21 further indicated, that a separate treatment of liquids provokes the same biological effect as a direct treatment at least for the kinpen. The same effect has been observed for the plasma jet studied in this work (see Fig.…”
Section: A Motivation Of Treatment Approachmentioning
confidence: 99%
“…When a low-temperature plasma jet was percutaneously irradiated to subcutaneous tumors of a mouse, gene expressions involved in organismal injury or abnormalities were altered [15]. Exposure of epithelial cells of human skin to an argon plasma jet increased gene expression of antioxidant enzymes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial reports that described nonthermal atmospheric pressure plasma, many plasma sources have been developed for medical, agricultural, and biological uses (Laroussi 1996;Fridman et al 2008;Isbary et al 2011;von Woedtke et al 2013). The medical applications of plasma include sterilization (Laroussi 1996;Graham and Mielnik 1997;Adler et al 1998;Iseki et al 2010), wound healing (Awakowicz et al 2009;Lademann et al 2010;Isbary et al 2012;Schmidt et al 2013;von Woedtke et al 2013;), blood coagulation (Kalghatgi et al 2007;Miyamoto et al 2016), and cancer treatments (Kieft et al 2004;Vandamme et al 2010;Keidar et al 2011;Jürgen Schlegel and Boxhammer 2013;Tanaka et al 2014b). Plasma medical science is a novel academic field that aims to elucidate the mechanisms of physiological outputs induced by plasma, including diagnosis using plasma, and comprehend the interactions between plasma and gas, liquids, and living bodies.…”
Section: Introductionmentioning
confidence: 99%